A regional paediatric rheumatology service. Issue 8 (August 1982) - Craft, A W; Hall, M
Abstract : A paediatric rheumatology clinic has been established in Newcastle since 1974, and 160 children had been referred to it by the end of 1980. The proportion of patients in each disease category is similar to that at the national centre at Taplow although far fewer patients with a positive anti-nuclear antibody test and fewer cases of chronic uveitus are seen. The importance of combining the skills of several disciplines is stressed.